PENGARUH KEBIJAKAN TUNJANGAN PERBAIKAN PENGHASILAN (TPP) TERHADAP SEMANGAT KERJA APARATUR PADA BADAN KEPEGAWAIAN DAN DIKLAT DAERAH KOTA MANADO - SOUISA, RIS (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : Based on Manado Mayor Regulation No. 05 of 2011 in the administration set to the Employee Income Supplement PNSD Regional Government within the city of Manado . Earnings improvement allowance policy is expected to boost morale within the apparatus of Manado City Government . By taking the test site Personnel Board and Regional Training Manado City , conducted research to determine the extent of the influence of policy in improving morale apparatus . This study uses quantitative methods . Sources of data / research respondents set as many as 30 employees were taken with the technique of sampling srtratified 55 employees Personnel Board and Regional Training Manado City . Instrument and data collection techniques used questionnaires and assisted with interviewing techniques . Data analysis used statistical regression analysis and product moment correlation , processed using the computer program SPSS version 12.0 for Windows .The study found : ( 1 ) the regression coefficient of earnings improvement allowance policy on morale and apparatus are significant posifive ( 2 ) the correlation coefficient and the coefficient of determination of income improvement allowance policy on morale is strong and apparatus signifikan.Berdasarkan research concluded that : ( 1 ) earnings improvement policy impact or a positive and significant impact on morale improved apparatus , (2 ) earnings improvement allowance policy makers have the power / morale significant influence on the apparatus . Based on the research results , it is suggested that the government continues the policy of the city of Manado can benefit the earnings improvement and continue to evaluate and make improvements to the weaknesses .Keywords : policy , morale.